Midwifery Care For A 5 Month 3 Day Old Baby With Mild Dehydration Diarrhea At Wajo Health Center - Sari, Wa Ode Nirmala; Sri Ernawati; Wa Ode Nurul Mutia (International Journal of Multidisciplinary Learners, 2024)
Background:Diarrhea is a disease characterized by a change in the shape and constitution of a soft to liquid stool, as well as an increase in frequency of more than 5 times a day. The purpose of preparing this final project report is to provide midwifery care to a baby aged 5 months and 3 days with mild dehydration diarrhea problems at Puskesmas Wajo Bau-Bau City. Subject: The research subject in this study was a 5-month-old NY baby. “M” with mild dehydration diarrhea problem at Wajo Community Health Center. The method used in this study uses a case study using Varney's seven steps and SOAP. Results: Subjective data obtained by the mother complained that her baby often defecated with very liquid constitution, the baby was hot and fussy. Objective data obtained General condition of the baby appears weak, component consciousness, body weight: 7.1 kilograms, head circumference: 37 cm, body length: 67 cm, sex: female. Vital signs: Pulse: 145 x/min, Breathing: 50 x/min, Temperature: 38.0 ̊C. The management carried out is to give the baby zinc supplements, give breast milk every time the baby is fussy, encourage the mother to keep her breasts clean before and after holding the baby. In conclusion, a midwifery care plan has been carried out in a baby aged 5 months and 3 days, namely by installing an IV and giving zinc supplements.